2020
DOI: 10.5195/jmla.2020.815
|View full text |Cite
|
Sign up to set email alerts
|

SPI-Hub™: a gateway to scholarly publishing information

Abstract: Background: Advances in the health sciences rely on sharing research and data through publication. As information professionals are often asked to contribute their knowledge to assist clinicians and researchers in selecting journals for publication, the authors recognized an opportunity to build a decision support tool, SPI-Hub: Scholarly Publishing Information Hub™, to capture the team’s collective publishing industry knowledge, while carefully retaining the quality of service.Case Presentation: SPI-Hub’s dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It is also worth noting that in addition to the population-level analysis features offered by the Word Cloud as described in our research collaboration for PheWAS analysis, the CKM also uses its capability of providing summary views of individual patient charts for other projects, such as our synthesized evidence provision services [ 14 , 26 ]. In response to providers’ complex clinical questions, information scientists consult the visual display of the Word Cloud to gain a holistic understanding of each patient’s comorbidities, medications, and other prominent clinical history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth noting that in addition to the population-level analysis features offered by the Word Cloud as described in our research collaboration for PheWAS analysis, the CKM also uses its capability of providing summary views of individual patient charts for other projects, such as our synthesized evidence provision services [ 14 , 26 ]. In response to providers’ complex clinical questions, information scientists consult the visual display of the Word Cloud to gain a holistic understanding of each patient’s comorbidities, medications, and other prominent clinical history.…”
Section: Discussionmentioning
confidence: 99%
“…In response to providers’ complex clinical questions, information scientists consult the visual display of the Word Cloud to gain a holistic understanding of each patient’s comorbidities, medications, and other prominent clinical history. This greatly facilitates our ability to generate tailored syntheses of the published evidence that are personalized to each specific patient case [ 26 ]. Additional applications of the Word Cloud and other AI tools are also under exploration at our center, including the use of AI for scaling the maintenance of evidence syntheses over time [ 27 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the Center for Knowledge Management at Vanderbilt University Medical Center (VUMC), our team of medical librarians has, for over twenty years, provided evidence syntheses of the biomedical literature to respond to clinicians' complex questions arising from clinical encounters. These questions were gathered initially through rounding with clinical teams and, since 2004, via a message basket service linked within the electronic health record (EHR) to facilitate clinicians' ability to send requests at the time and place when they most need an answer [10][11][12][13][14]. A previous study found high levels of physician satisfaction with evidence summaries provided by our team [15].…”
Section: Introductionmentioning
confidence: 99%
“…Journal selection is thus a difficult balancing act that precludes a one-size-fits-all ranking system. To support researchers, tools have been developed that match manuscripts with journals by manuscript title, abstract, and (in some cases) citations [6][7][8]. These tools vary in matching strategy, in the journal information they provide (such as publication speed, processing charges, and impact metrics), and in which journals are included (e.g., well-marketed tools developed by Elsevier, Springer, Wiley, and IEEE evaluate only the journals that they publish).…”
Section: Introductionmentioning
confidence: 99%